ANALYSIS OF THE ADVANTAGES AND DISADVANTAGES OF GOTO SHARES ON THE INDONESIAN STOCK EXCHANGE FOR INVESTMENT - Afifahtus Syaleha; Muhammad Ilham J; Tohonan Rohani Silaban; I Made Suparta (Nirta Learning Centre, 2025)
This study aims to analyze the advantages and disadvantages of PT GoTo Gojek Tokopedia Tbk (GOTO) shares as an investment option on the Indonesia Stock Exchange using the literature study method. GOTO shares are the focus because of their role as one of the largest technology companies in Indonesia resulting from the merger between Gojek and Tokopedia. Through a literature review from various sources such as scientific journals, news articles, and other secondary data, this study found that GOTO shares have advantages in the form of longterm growth potential and a broad digital ecosystem. However, there are also disadvantages such as high price volatility, profit uncertainty, and risks from the regulatory and market competition side. The results of this study are expected to be a reference for prospective investors who want to understand more about the risks and opportunities of investing in technology company shares in Indonesia.